25 DE DEZEMBRO: SIMBOLISMOS E APROXIMAÇÕES ENTRE OS DEUSES APOLO, HÉLIOS, MITRA E JESUS CRISTO UMA ANÁLISE EM MITOLOGIA COMPARADA - Feitosa, Sergio Paulo de Melo (2013)
The Winter Solstice demonstrates the importance of the sun as an element bearer of life, in countless European and eastern cultures. The Greeks, on a rather distinct way in regard of other peoples, fashioned their mythic through worshipping two sun gods, that interchanged in the beliefs and cults of this people: Helios and Apollo. The Latin, who absorbed part of the Greek myth in worshipping these divinities, brought progressively another sun god to be worshipped: Mithra. Christianity, that migrates from its local and cultural source to the Latin cities, especially Rome, in the first Century, causes and faces a constant combat with pagan beliefs, especially those rooted in solar deity beliefs, and progressively manage a supremacy, to the point where the non-Christian beliefs are suppressed, a process initiated with the emperor Constantine and finished with Theodosius I. However, the imaginary of the cultures overcome by Christianity couldn t be completely eliminated; pagan gods are established in several elements of the new religion, like in the celebration of the birth of Jesus Christ, defended by the Church as held in December the 25th. The period, actually, was known in the millennium before the emergence of Christendom as the date of birth of the god Mithras, and close to the Winter Solstice, where the gods Apollo and Helios were worshipped, transformed in the Latin culture as the cult of the Sun Invictus.